Mesenchymal stem cells reside in a vascular niche in the decidua basalis and are absent in remodelled spiral arterioles. Issue 3 (March 2015) - Kusuma, G.D.; Manuelpillai, U.; Abumaree, M.H.; Pertile, M.D.; Brennecke, S.P.; Kalionis, B.
Abstract Introduction Maternal decidua basalis tissue attached to the placenta following delivery is a source of decidual mesenchymal stem cells (DMSCs). The in vitro characteristics of DMSCs have been partly defined but their in vivo function(s) are poorly understood. The anatomic location, or niche, provides clues regarding potential in vivo function(s) of DMSCs, but the niche has not been described. Methods Cells were isolated from the decidua basalis and flow cytometric analyses showed the expected phenotypic profile for MSC cell surface markers. In vitro, the cells differentiated into adipocytes, osteocytes, and chondrocytes. DMSCs were then stained with antibodies by immunofluorescence detection. Results Immunocytochemistry revealed that DMSCs were positive for FZD-9, STRO-1, 3G5, and α-SMA as expected and lacked expression of vWF and Ck7. Fluorescence in situ hybridization analysis showed the cultured cells were of maternal origin. Immunofluorescence was carried out on placental bed biopsies using the FZD-9, STRO-1, 3G5, and α-SMA antibodies. DMSCs were located in the vascular niche in decidua basalis. Immunofluorescence with antibodies to FZD-9, Ck7 and vWF revealed DMSCs in the vascular niche surrounding intact non-transformed spiral arterioles but DMSCs were absent in fully transformed spiral arterioles. Discussion Spiral arteriole remodelling is a critical feature of human pregnancy. The DMSC niche was investigated in fully transformed and non-transformed spiral arterioles. DMSCs have not been previously implicated in spiral arteriole remodelling. The absence of DMSCs around fully transformed spiral arterioles suggests they are a target for replacement or destruction by invading placental extravillous trophoblast cells, which carry out spiral arteriole remodelling.